NUT carcinoma of the submandibular gland: A case report - Simone Rota; Pasquale Quattrone; Giovanni Centonze; Gianpaolo Dagrada; Arianna Ottini; Elena Colombo; Imperia Nuzzolese; Giuseppina Calareso; Marzia Franceschini; Nicola Alessandro Iacovelli; Federica Perrone; Elena Tamborini; et al. (Cancer Reports, 2023)
Abstract Background NUT carcinoma (NUTc) is a rare and aggressive malignant epithelial tumor characterized by rearrangement of the NUT gene on chromosome 15q14. Methods In this article, we present the fifth case worldwide of a young woman affected by a NUTc arising from a submandibular gland, presenting as a rapidly evolving mass. She underwent a right scialoadenectomy and received the initial diagnosis of high‐grade mucoepidermoid carcinoma. Due to evidence of local recurrence at magnetic resonance imaging 1 month later, a subsequent right radical neck dissection was performed. The patient then sought a second opinion at our cancer center and finally received the correct diagnosis of NUT carcinoma. Given the well‐known aggressive behavior of this neoplasm, as well as clinical and radiological features, she underwent adjuvant chemo‐radiation (intensity‐modulated radiotherapy + concurrent chemotherapy with cisplatin). Results After a disease‐free interval of 2.6 months, a widespread metastatic disease led to rapid deterioration of performance status and patient death in a few weeks after metastatic onset. Conclusions We presented a case of NUTc arising from salivary gland aiming to improve the knowledge of this rare malignancy. First, we pointed out that in the setting of rare tumors like salivary gland cancers, the diagnosis should be obtained by expert pathologists, and patients should be referred to tertiary cancer centers for their clinical management. Second, molecular profiling may help to identify possible druggable targets that may be exploited to treat patients suffering from this aggressive malignancy. Sharing the molecular data provided in this case will be useful for further research.